2018
DOI: 10.1016/j.jaad.2018.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma staging: Varying precision and terminal digit clustering in Breslow thickness data is evident in a population-based study

Abstract: The Norwegian recommendation of measurement to the nearest 0.1 mm was not followed. Terminal digit clustering was marked, with consequences for T category. Pathologists, clinicians, and epidemiologists should know that clustering of thickness data around T category cut points can impact melanoma staging with consequent effect on patient management and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…PASI-75 was achieved in 86% and 85% of patients receiving brodalumab (210 mg dose) in the two separate studies. According to pooled long-term data from AMAGINE-2 and −3, >60% of patients receiving any dose of brodalumab for >2 years (108 weeks) achieved PASI 100 17. A further pooled analysis of AMAGINE-2 and −3 data showed that, in patients who received brodalumab 210 mg every 2 weeks for 52 weeks, PASI 100 was achieved in 63.4% and 62.9% of patients at 52 and 108 weeks, respectively 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PASI-75 was achieved in 86% and 85% of patients receiving brodalumab (210 mg dose) in the two separate studies. According to pooled long-term data from AMAGINE-2 and −3, >60% of patients receiving any dose of brodalumab for >2 years (108 weeks) achieved PASI 100 17. A further pooled analysis of AMAGINE-2 and −3 data showed that, in patients who received brodalumab 210 mg every 2 weeks for 52 weeks, PASI 100 was achieved in 63.4% and 62.9% of patients at 52 and 108 weeks, respectively 18.…”
Section: Discussionmentioning
confidence: 99%
“…According to pooled long-term data from AMAGINE-2 and −3, >60% of patients receiving any dose of brodalumab for >2 years (108 weeks) achieved PASI 100 17. A further pooled analysis of AMAGINE-2 and −3 data showed that, in patients who received brodalumab 210 mg every 2 weeks for 52 weeks, PASI 100 was achieved in 63.4% and 62.9% of patients at 52 and 108 weeks, respectively 18. In patients who received ustekinumab for 52 weeks, PASI 100 was achieved in 42.3% of patients, but after switching to brodalumab 210 mg every 2 weeks at week 52, PASI 100 increased to 62.5% at week 108 18…”
Section: Discussionmentioning
confidence: 99%
“…Preferential overrepresentation of certain terminal digits (terminal digit preference) is a well-known source of measurement error in medicine, including the measurement of malignant tumors [1][2][3]. Some evidence suggests that pathologists measuring breast tumor diameter favor terminal digits of zero or five, though few studies have evaluated this type of measurement error as a primary objective [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies have documented that provision of care according to national guidelines positively influence clinical outcomes. Effects from refined diagnostics, e.g., increasing use of preoperative MRI and improved quality of pathology reports have been demonstrated to influence resection rates, local recurrence rates and survival in e.g., breast cancer, colorectal cancer, gastroesophageal cancer and melanoma [30][31][32][33][34][35][36][37][38][39]. In e.g., colorectal cancer, lung cancer and urinary bladder cancer, registry data have been used to demonstrate increasing survival rates in large cohorts [30,34,[39][40][41][42].…”
Section: Monitoring Changing Principles Of Carementioning
confidence: 99%